IMPROVING STUDENTS’ READING COMPREHENSION THROUGH YOUTUBE AT GRADE VII OF SMPN 3 BUKIT BATU - Lismameriati Hutagaol (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
Learning during the pandemic that supports 21st century learning uses online learning and the media in the form of YouTube which has been prepared by the teacher in advance. The aim of this research was to improve the students’ reading comprehension at grade VII of SMPN 3 Bukit Batu. This research used classroom action research in two cycles consisting of 2 lessons per cycle with a total of 27 students. The results of the research before the action obtained an average of 65.81 with the number of students completed the KKM were 13, classically 48%. In the first cycle, learning was carried out by using youtube learning media so that an average of 70.2 was obtained with the number of students who completed were 20 people, with the percentage of classical completeness reaching 74.1%. Meanwhile, in the second cycle, an average of 83.5 was obtained with the number of students who completed were 26 people with the percentage of classical completeness reached 96.3%. The results of teacher observations found that the average cumulative results of the assessment on learning observation activities in the first cycle was 66.7 and increased in the second cycle by 91.7. Thus, it was concluded that the use of youtube media was able to improve students' reading comprehension.